Accuracy of Magnetic Resonance Imaging in Prenatal Diagnosis of Choledochal Cysts: A Single-Center Retrospective Analysis - Huiying Wu; Jinsheng Tian; Hehong Li; Hongsheng Liu; Yutao Liu; Lianwei Lu; Xiwen Chen; Xiaochun Zhang; Wenbiao Xu (International Journal of Clinical Practice)
Background. The purpose of this study is to evaluate the accuracy of prenatal MRI in diagnosing choledochal cysts (CDC), evaluate the sensitivity and specificity of MRI signs in the diagnosis of fetal CDC, and first compare the trend of size of CC between prenatal and postpartum. Methods. A total of 18 fetal who were diagnosed with CDCs through prenatal MRI were enrolled in the study. We summarized and analyzed the prenatal clinical data and prognosis information of prenatal and postpartum surgery, then compared the sensitivity, specificity, and diagnostic accuracy of various signs of MRI and postpartum MRCP diagnosis of CC. Finally, we tried to compare the earliest prenatal detection of common bile duct cysts with the size of surgery, and calculated the growth rate of common bile duct cysts for the first time. Results. All 18 patients were delivered in our institution. Among these patients, 14 were confirmed with CDCs after postpartum surgery, two patients had CDCs that disappeared, and two patients were confirmed with cystic biliary atresia (CBA) through the Kasai operation. Furthermore, 13 patients with CDCs and two patients with CBA underwent MRCP before the operation, and one patient with CDCs ruptured at birth and underwent ultrasound diagnosis. The sensitivity and diagnostic compliance of prenatal MRI signs for the location were higher when compared to postnatal MRCP (100% vs. 76.9% and 83.3% vs. 66.7%): the cyst was located at the porta hepatis, which was higher than the lowest edge of the liver, and parallel to the hepatoduodenal ligament. Conclusion. Prenatal MRI is higher than that of US for diagnosing CDCs, specifically in identifying the location of the cyst and confirming the origin of the cyst. The length, width, and size of the CDC become slightly bigger in our study.